HUNTINGTON DISEASE: CURRENT ADVANCES IN PATHOGENESIS AND RECENT THERAPEUTIC STRATEGIES (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Huntington's disease (HD) is an inherited autosomal, progressive neurodegenerative disorder associated with involuntary abnormal movements (chorea), cognitive impairments and psychiatric disturbances. HD is caused by an abnormal expansion of a CAG region located in exon 1 of the gene encoding the huntingtin protein (Htt) and is the causative factor in the pathogenesis of HD. However, recent evidences show that impaired mitochondrial function plays a key role in the pathogenic processes of the desease. The underlying mechanisms by which mutant Htt (mHtt) causes HD have not been fully elucidated, however mutant Htt can impair mitochondrial function by dysregulation of transcriptional processes, calcium dyshomeostasis, and defective mitochondrial bioenergetics. Mutant Htt induce intracellular Ca2+ in neurons affected by HD and increased intracellular Ca2+ excessively enter mitochondria and induce to open the mitochondrial permeability transition pores (mPTP), leading to decreased mitochondrial ATP, and neuronal death. Transcriptional processes regulated by peroxisome proliferator-activated receptor γ (PPARγ) coactivator-1α (PGC-1α), which are critical for mitochondrial biogenesis, have also been shown to be impaired in HD. This review article discusses current developments, in determining the role of mitochondrial morphological and functional abnormalities contributing to the pathogenesis of HD and also discusses the current other possible therapeutic interventions.